The Model of Tourism Village Development in the District of Tabanan - Widiati, Ida Ayu Putu; Suryani, Luh Putu; Permatasari, Indah (Fakultas Hukum, Universitas Warmadewa, 2019)
The growth in the tourism sector in Bali has certainly delivered positive adavantages to particularly the enhancement of community prosperity. In encouraging the prevalence of opportinity take to make efforts to enhance the community welfare and empowerment, tourism villages can be one of the useful facilities to help increase the community economy. The proposition explored in this study is that in Tabanan there are still tourism villages which could not develop optimally. Therefore, this study is designed to examine the factors that hinder the optimal development of the village in question. Moving on from the obstacles that have been found, a solution is raised to help overcome the delay in development. The solution is to introduce and implement a model for developing tourism villages in Tabanan. This study makes use of empirical legal research with two types of data: primary and secondary data. The study sample is determined by applying a non-probability/non-random sampling technique. The model of tourism village development in Tabanan is based on empowerment of local communities (community-based tourism). This model of tourism village development is inseparable from religious values, the living culure in the community, and the preservation and quality of the environment. By the application of this model, sustainable tourism development is expected to be realized.